Direct Identification of Mycobacteria from MB/BacT Alert 3D Bottles: Comparative Evaluation of Two Commercial Probe Assays - Scarparo, Claudio (American Society for Microbiology, 2001)
The new INNO-LiPA Mycobacteria (Innogenetics, Ghent, Belgium), a reverse-hybridization-based line probe assay, and the AccuProbe assay (Gen-Probe Inc., San Diego, Calif.) were applied to MB/BacT Alert 3D (MB/BacT) system (Organon Teknika, Boxtel, The Netherlands) culture bottles and evaluated for mycobacterial identification. From 2,532 respiratory and extrapulmonary specimens submitted for culture, 168 were flagged positive by the MB/BacT system and promptly evaluated for identification (within 24 h). Each of 163 vials grew one mycobacterial isolate, including Mycobacterium tuberculosis complex (n = 73), M. avium complex (n = 3), M. avium (n = 8), M. intracellulare (n = 5), M. kansasii (n = 15), M. gordonae (n = 8), M. malmoense (n = 3), M. chelonae (n = 13), M. abscessus (n = 2), M. xenopi (n = 11), M. scrofulaceum (n = 2), M. fortuitum (n = 7), M. terrae (n = 3), M. simiae (n = 2), M. celatum (n = 3), M. flavescens (n = 1), M. interjectum (n = 1), M. bohemicum (n = 1), and M. pulveris (n = 2). Five cultures yielded mixed growth of two mycobacterial species: M. tuberculosis complex plus M. gordonae (n = 2), M. tuberculosis complex plus M. chelonae (n = 1), M. tuberculosis complex plus M. xenopi (n = 1), and M. avium plus M. chelonae (n = 1). In testing of one-isolate vials, both systems showed excellent sensitivity and specificity for all species and complexes for which they are licensed (nine for INNO-LiPA Mycobacteria versus six for AccuProbe). There were minor discrepancies in results for two isolates identified by INNO-LiPA Mycobacteria as M. avium - M. intracellulare - M. scrofulaceum (MAIS) complex and by AccuProbe as M. intracellulare. In testing of two-isolate vials, INNO-LiPA Mycobacteria correctly identified all isolates, while the AccuProbe assay failed to identify three M. tuberculosis complex isolates and one M. avium isolate. The AccuProbe assay was completed within 2 h, while INNO-LiPA Mycobacteria required a 6-h period. In our opinion, INNO-LiPA Mycobacteria offers the following advantages: (i) it contains a genus-specific probe that, in addition to being used in genus identification, may be used as an internal control for both the amplification and hybridization steps; (ii) it simultaneously identifies M. tuberculosis complex, MAIS complex, and seven other mycobacterial species, even from mixed cultures; (iii) its mycobacterial DNA amplification ensures reliable results independent from the concentration of viable microorganisms; and (iv) it genotypically identifies M. kansasii and M. chelonae. In conclusion, even though INNO-LiPA Mycobacteria is considerably less easy to use than AccuProbe, requiring personnel skilled in molecular biology techniques, it represents an excellent approach for routine identification of frequently encountered mycobacteria.